Is Dental Treatment Safe in Pregnancy? A Dentist’s Opinion Survey in South India - Naidu, Guntipalli M; Ram, K Chaitanya; Kopuri, Raj Kumar Chowdary; Prasad, S Eswar; Prasad, Durga; Babburi, Suresh (Journal of Orofacial Research, 2013)
Background: Oral health of pregnant patients is considered as an essential component of the overall health of the mother and the developing fetus. The aim of this study was to know dentist perspective regarding treatment options in pregnant patients. Materials and methods: A cross-sectional survey was conducted among dentists of south India by mailing a selfadministered questionnaire to collect data on management choices of the pregnant dental patient related to treatment practices and therapeutic choices of dentists and also their sociodemographic and practice characteristics. Results: A total of 726 questionnaires was collected. Around 28.5% of the participants took radiographs for pregnant patients. Mostly, all the surveyed dentists would extract a non-restorable painful tooth during pregnancy. Around 89.3% prescribe a mouthwash and 37% would perform root planning and periodontal surgery for gingival bleeding and calculus deposits. Majority of the dentists (92.9%) prescribe amoxicillin. By far paracetamol was the most popular analgesic agent (91%). The majority of the dentists (62.3%) would use plain xylocaine Conclusion: There is a clear lack of knowledge about the appropriate management of the pregnant dental patient among the surveyed dentists regardless of their sociodemographic and practice characteristics necessitating continuous education on the dental management of pregnant dental patient.